Petrogenesis of Metamorphic Rock in the Mukito Formation at Sorawolio Region, Bau-Bau City, Buton Island, Southeast Sulawesi Province, Indonesia - Hasria; La Hamimu; Prawira, Andi Bhaskara; Arisona; Juarzan, Laode Ihksan; Sara Septiana (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The petrogenesis study of the metamorphic rocks of the Mukito Formation was carried out in the Sorawolio area, Bau-Bau City, Buton Island, Southeast Sulawesi Province, Indonesia. This research area is included in the southern part of the Buton sheet with coordinates S 5⁰23'40.8'' and E 122⁰43'44.9''. The aim of this research is to determine the petrogenesis of metamorphic rocks which includes determining the rock type, facies, type of metamorphism and protolith. The research methods used include megascopic and microscopic analysis of rocks in the form of petrographic analysis which includes identification of mineral content and rock texture and geochemical analysis in the form of XRF tests to determine the main oxide elements in metamorphic rock samples. Data obtained from the results of petrographic analysis show that the research area consists of several types of metamorphic rock, namely serpentinite, phyllite, chlorite schist, hornblende schist and amphibolite. The metamorphic rocks in the research area are included in the greenschist facies and amphibolite facies with regional metamorphism types as well as protoliths from igneous rocks in the form of basalt rock which were formed in the tholeiitic oceanic-island tectonic environment which is a convergent complex characterized by continental origin in the magma series in the form of the tholeiitic series and calc -alkaline series.